Clinical application of whole-genome sequencing in the management of extensively drug-resistant tuberculosis: a case report - Bugwesa Z. Katale; Sylvia Rofael; Linzy Elton; Erasto V. Mbugi; Stella G. Mpagama; Daphne Mtunga; Maryjesca G. Mafie; Peter M. Mbelele; Charlotte Williams; Happiness C. Mvungi; Rachel Williams; Gulinja A. Saku; et al. (BMC, 2024)
Abstract Background Whole-genome sequencing (WGS)-based prediction of drug resistance in Mycobacterium tuberculosis has the potential to guide clinical decisions in the design of optimal treatment regimens. Methods We utilized WGS to investigate drug resistance mutations in a 32-year-old Tanzanian male admitted to Kibong'oto Infectious Diseases Hospital with a history of interrupted multidrug-resistant tuberculosis treatment for more than three years. Before admission, he received various all-oral bedaquiline-based multidrug-resistant tuberculosis treatment regimens with unfavourable outcomes. Results Drug susceptibility testing of serial M. tuberculosis isolates using Mycobacterium Growth Incubator Tubes culture and WGS revealed resistance to first-line anti-TB drugs, bedaquiline, and fluoroquinolones but susceptibility to linezolid, clofazimine, and delamanid. WGS of serial cultured isolates revealed that the Beijing (Lineage 2.2.2) strain was resistant to bedaquiline, with mutations in the mmpR5 gene (Rv0678. This study also revealed the emergence of two distinct subpopulations of bedaquiline-resistant tuberculosis strains with Asp47f and Glu49fs frameshift mutations in the mmpR5 gene, which might be the underlying cause of prolonged resistance. An individualized regimen comprising bedaquiline, delamanid, pyrazinamide, ethionamide, and para-aminosalicylic acid was designed. The patient was discharged home at month 8 and is currently in the ninth month of treatment. He reported no cough, chest pain, fever, or chest tightness but still experienced numbness in his lower limbs. Conclusion We propose the incorporation of WGS in the diagnostic framework for the optimal management of patients with drug-resistant and extensively drug-resistant tuberculosis.